Anxiety unplugged: Effectiveness of an unguided, transdiagnostic, web-based intervention for anxiety disorders—A randomized controlled trial - Anna Baumeister; Lea Schuurmans; Steffen Moritz (Internet Interventions)
Background and aim: Anxiety disorders are the most common psychiatric condition, yet few patients receive adequate treatment, primarily due to high barriers to treatment (e.g., long waiting times, fear of stigmatization). Internet-based cognitive behavioral therapy (iCBT) programs have emerged as a promising approach to addressing this treatment gap, demonstrating effectiveness across various anxiety disorders. However, only a few studies have specifically addressed unguided iCBT. This trial investigated a six-week transdiagnostic unguided iCBT intervention designed to reduce anxiety and related symptoms. Methods: Randomized to an intervention group and a waitlist control group with care as usual, 318 participants were included in the analyses, which used ANCOVAs to assess changes in symptom severity of anxiety (primary) and related secondary outcomes (stress, depression and anxiety, quality of life, self-esteem). Results: Significant post-intervention reductions in anxiety, stress, and depression were found in the intervention group compared to controls at small to medium effect sizes (|Hedges's g| = 0.27–0.35). Concurrent ongoing psychotherapy negatively modified the treatment effect. Conclusion: The iCBT program proved effective overall in reducing anxiety and anxiety-related symptoms compared to care as usual. However, the program did not appear to have an add-on effect for individuals who were simultaneously receiving conventional psychotherapy. Further research is needed to investigate the effects in this subgroup in more detail.